PREVALENSI OBESITAS PADA ANAK USIA SD MENURUT IMT/U DI SD NEGERI PLOSO II NO 173 SURABAYA - KHUSNUL YAQIN, MOCHAMAD (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract Elementary School No. Ploso II. 173 is located in the eastern part of the sub-district of Surabaya cider farms, of every class there are some students who are overweight. One of the causes of obesity is due to the influence of lifestyle, a lifestyle far different surabaya child with a few years ago, the proliferation of stores, depots and eat a variety of snacks that do not make children more aware of that has been consumed. The pupose of this study is to determine the prevalence of obesity in primary school age children according to IMT/U and the research method used is a type of survey research. Subjects in this study were student of SDN Ploso II consisting of 503 children using the percentage of data analysis. From the analysis research got the result of student who are very thin as many as 8 children (2%), student who are skinny as many as 17 children (3%), student who otherwise normal as many as 387 children (75%), student otherwise fat as much as 94 children (18%), and students who were obese were 11 children (2%). Then the prevalence of obesity in primary school age children in SDN Ploso II Surabaya by 2 % and most likely to become obese is obese category student by 18% and the factors that affect the child is obese parents social status, nutrition excessive, family genetic and physical activity conducted by the students. Keywords : Prevalence of Obesity In Childhood According to IMT/U